Intervenção psicossocial sobre violência de gênero com estudantes universitárias: estudo de viabilidade - Dionísio, Maria Beatriz Reis (Universidade Federal de São Carlos, 2022)
Gender violence has been a growing problem within Brazilian universities and still little studied in the country. However, it has been increasingly urgent to think about actions aimed at confronting this violence and combating gender inequalities in this scenario. Among the possible mechanisms for coping with violence, group context intervention for women who were exposed to violent situations stands out. This dissertation aimed to develop, conduct and evaluate the feasibility of a remote psychosocial intervention on gender violence with university students. To achieve the first objective, a review of the national and international literature on interventions on gender violence in the context of the university was carried out. Searches were carried out in the databases: Scopus, Lilacs, Scielo, PubMed, and Web of Science from December 2020 and January 2021 and resulted in 524 articles, however only one article was considered eligible to be analyzed. The study aimed to examine the use of the Photovoice method as a therapeutic intervention with university women who were victims of sexual violence and who presented symptoms of Post-traumatic Stress Disorder, obtaining promising results regarding the therapeutic effects of the method. The second study describes the remote intervention with the target population. Two students participated in the research, initially a synchronous interview was carried out with the researcher in which they answered the Questionnaire of Stressful Events, the Transversal Scale of Symptoms Level 1 Self-Applicable of the DSM-5 Adults, Difficulties in Emotion Regulation Scale - DERS, and the Questionnaire of Emotional Regulation as a pre-test and answered them again at the end of the intervention. Subsequently, 8 90-minute weekly synchronous meetings were held. The protocol used consisted of using psychoeducation on gender violence, working on the victims' self-knowledge/self-esteem, as well as the support network and, above all, emotional regulation. All meetings were recorded and later transcribed for analysis of the intervention process. To verify the rate of significant clinical change, the JT method was conducted. The results obtained indicated that there was a reliable positive change in the total score of the Difficulty in Emotional Regulation Scale that can be attributed to the intervention. The protocol used showed the potential to be rethought in its forms of application, however, despite the high acceptability and adherence of the participants, the intervention was not satisfactory in terms of other feasibility criteria, such as demand.
Psychosocial intervention on gender violence with university students: a feasibility study
Keywords: Violência de gênero; Universidade; Intervenção; Violência contra mulher; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA